Nanoporous Titanium (Oxy)nitride Films as Broadband Solar Absorbers - Bricchi, Beatrice R; Mascaretti, Luca; Garattoni, Simona; Mazza, Matteo; Ghidelli, Matteo; Naldoni, Alberto; Li Bassi, Andrea (ACS applied materials & interfaces, 2022)
Broadband absorption of solar light is a key aspect in many applications that involve an efficient conversion of solar energy to heat. Titanium nitride (TiN)-based materials, in the form of periodic arrays of nanostructures or multilayers, can promote significant heat generation upon illumination thanks to their efficient light absorption and refractory character. In this work, pulsed laser deposition was chosen as a synthesis technique to shift metallic bulk-like TiN to nanoparticle-assembled hierarchical oxynitride (TiOxNy) films by increasing the background gas deposition pressure. The nanoporous hierarchical films exhibit a tree-like morphology, a strong broadband solar absorption (∼90% from the UV to the near-infrared range), and could generate temperatures of ∼475 °C under moderate light concentration (17 Suns). The high heat generation achieved by treelike films is ascribed to their porous morphology, nanocrystalline structure, and oxynitride composition, which overall contribute to a superior light trapping and dissipation to heat. These properties pave the way for the implementation of such films as solar absorber structures.
Keywords: solar−thermal conversion; titanium oxynitride; pulsed laser deposition; hierarchical nanostructures; broadband solar absorption